Phylogeography based on the nuclear ribosomal DNA internal transcribed spacer region of native Miscanthus sinensis (Poaceae) populations in Japan. Issue 4 (21st October 2014) - Hayakawa, Hiroshi; Akasaka, Maiko; Shimono, Yoshiko; Kurokawa, Shunji; Nishida, Tomoko; Ikeda, Hiroaki; Wakamatsu, Toru
<x xml:space="preserve">Abstract</x> Nucleotide sequence variations were investigated with respect to the geographical distribution patterns of Miscanthus sinensis populations that were sampled from 26 Japanese national parks and three populations of the Ryukyu Islands. Twelve homozygous sequences in the nuclear ribosomal DNA internal transcribed spacer region were detected. The populations of M. sinensis in mainland Japan mainly were composed of a monophyletic group with a symapomorphic character, whereas those in the Ryukyu Islands included a polyphyletic group. Only an internal transcribed spacer haplotype with a plesiomorphic character was found in both mainland Japan and the Ryukyu Islands. Thus, no clear geographical isolation was observed in this species. These facts might be caused by the ability of M. sinensis as a pioneer plant to have a high migration potential and high gene flow by outcrossing. On the basis of the results of this study (nuclear ribosomal DNA) and the previous study (chloroplast DNA), a phylogeographical history of M. sinensis was presumed where the ancestral and derived lineages were distributed in the southern and northern regions of Japan, respectively, without strict geographical isolation.